Macrophages and inflammatory mediators in pulmonary injury induced by mustard vesicants. Issue 1 (28th June 2016) - Malaviya, Rama; Sunil, Vasanthi R.; Venosa, Alessandro; Vayas, Kinal N.; Businaro, Rita; Heck, Diane E.; Laskin, Jeffrey D.; Laskin, Debra L.
Abstract : Sulfur mustard (SM) and nitrogen mustard (NM) are cytotoxic alkylating agents that cause severe and progressive injury to the respiratory tract, resulting in significant morbidity and mortality. Evidence suggests that macrophages and the inflammatory mediators they release play roles in both acute and long‐term pulmonary injuries caused by mustards. In this article, we review the pathogenic effects of SM and NM on the respiratory tract and potential inflammatory mechanisms contributing to this activity.